Micro-finance Access for Women Entrepreneurs in Makassar: A Phenomenological Study of Barriers and Survival Strategies - Amin, Andi Mustika (PT Maju Malaqbi Makkarana, 2025)
This study examines how women entrepreneurs in Makassar negotiate access to and use of microfinance in a limited socio-economic environment, using a humanistic economic perspective to promote dignity, agency, and relational outcomes. Qualitative interviews reveal that while microcredit supplies the short—term liquidity essential for day-to-day operations, formal lending is constrained by collateral demands, procedural complexity, the gender asset gap, and time poverty-forces that drive many women toward informal lending, Diversified Income Strategies, and emerging digital channels. Evidence from digital finance and platform research suggests that successful FinTech adoption depends on trust, usability, security, and perceived value, which shape whether digital options complement or replace conventional microfinance in local contexts. Field experiments on online mentoring show that carefully designed digital interventions can increase women's willingness to engage with mentor networks, but effective connections require platform support and user learning that reduces onboarding friction and builds trust. Complementary policy tools-small matching grants, time-saving subsidies (eg, childcare), and targeted business advisors-have been shown to reduce information and time constraints, increase formal credit acceptance, and improve corporate performance among female entrepreneurs, especially those with prior experience. Together, these findings argue for an integrated policy package that streamlines formal lending, embeds relational support and capability development, and leverages trustworthy digital interfaces so that microfinance improves economic resilience and human dignity for women-led microenterprises in Makassar.